Thermogravimetric Analysis of Eucalyptus Leaves as An Alternative Fuel for Rural Areas - Maarasyid, Cici; Idayu, Ida; Zulfansyah, Zulfansyah; Israyandi, Israyandi; Legawati, Lisa; Ermal, Dini Aulia Sari; Fithry, Dwi Annisa (Semesta Teknika, 2024)
The utilization of biomass waste as a substitute for conventional energy sources has gained popularity, and one possible source is the litter generated by eucalyptus plantations. The present study used thermogravimetric analysis (TGA) gain insight into the thermochemical characteristics of eucalyptus leaves. It was identified by heating the sample in a nitrogen environment from ambient temperature to 850oC at a rate of 10 oC/minute. Eucalyptus leaves have a high volatile matter (VM) content and a calorific value (CV) of 17.26 MJ/kg, according to the ultimate and proximate analysis. Additionally, the TGA results showed that eucalyptus leaves had a lower ignition temperature than other biomasses. Eucalyptus leaves began to devolatilize at 119 oC, reaching a peak temperature of 326 oC, and losing 68% of their weight as a result.